Effects of HDAC inhibitors on spatial memory and memory extinction in SPS-induced PTSD rats - Ahmad Mohammadi-Farani; Ali Pourmotabbed; Yazdan Ardeshirizadeh (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Neurobiological changes in memory processes seem to play a role in the pathophysiology of post-traumatic stress disorder (PTSD). Memory itself is influenced by PTSD, too. Histone deacetylase inhibitors (HDAIs) have shown promising results in the extinction of fear-related memories in animals and hence they seem to be important for the treatment of PTSD. Data are scarce about the effect of HDAIs in spatial memory formation/extinction in PTSD models. The main goal of the present work is to find the effect of sodium butyrate (NaBu), as an HDAI, on spatial memory and spatial memory extinction in rats exposed to single prolonged stress procedure (SPS). Experimental approach: Different doses of NaBu were administered subcutaneously for 7 days in different groups of rats after SPS procedure. Learning, memory, and extinction of memory were evaluated in the Morris water maze test of spatial memory in 6 consecutive days. Findings / Results: The results show that NaBu (0.5 mg/kg) alleviates impaired learning and memory in SPS rats. It also facilitates the extinction of newly formed memory in the animals. Conclusion and implications: Our data suggest that the administration of HDAIs after a traumatic experience can prevent the aversive effects of SPS on spatial memory. It also reinforces the notion that extinction of spatial memory involves the same or similar brain circuitry that is involved in the extinction of fear memories in PTSD patients.